The prevalence of all types of diabetes and pre‑diabetes in the Eastern Mediterranean countries: a meta‑analysis study - Asra Moradkhani; Mobin Azami; Pardis Mohammadzadeh; Hamid Reza Baradaran; Lotfolah Saed; Kianush Asvad; Rojina Kakaei; Sorour Khateri; Farhad Moradpour; Yousef Moradi (BMC Endocrine Disorders)
Abstract Background and aim Given the high prevalence, incidence, and impact on Disability-Adjusted Life Years (DALYs) associated with diabetes, coupled with the limited availability of meta-analysis studies examining its prevalence in the Eastern Mediterranean Regional Office (EMRO) countries, the main objective of this study was to investigate the combined prevalence of type 1 (T1DM) and type 2 diabetes (T2DM), gestational diabetes, and pre-diabetes within the Eastern Mediterranean region. Methods To implement a comprehensive search strategy aligned with the objectives of this meta-analysis, searches were conducted across international databases, including PubMed (Medline), Scopus, Embase, Web of Science, and the Cumulative Index to Nursing and Allied Health Literature (CINHAL) from January 1967 to December 2022. The quality of the selected studies was assessed using the JBI critical appraisal checklist for analytical cross-sectional studies. Subgroup analyses were conducted based on factors such as gender, country, geographic area, criteria for diagnosis, and Gross Domestic Product (GDP) level. Results Out of 5,238 primary studies initially screened, 186 articles were included in the meta-analysis. The pooled prevalence of diabetes was found to be 15% (95% CI: 13 – 16%), of which 6% (95% CI: 4 – 7%) represented undiagnosed cases, while 8% (95% CI: 7 – 10%) were known cases. The prevalence of T2DM was 13% (95% CI: 11 – 16%), while T1DM was found to have a prevalence of 1% (95% CI: 1 – 2%). Pre-diabetes had a pooled prevalence of 15% (95% CI: 13 – 18%), with impaired glucose tolerance (IGT) and impaired fasting glycemia (IFG) representing 9% (95% CI: 7 – 11%) and 8% (95% CI: 6 – 11%) of cases, respectively. The prevalence of gestational diabetes mellitus (GDM) was found to be 11% (95% CI: 9 – 14%) in the EMRO. Conclusion The findings emphasize the need for enhanced healthcare programs, including early screening, effective management, and lifestyle interventions such as healthy eating and physical activity. The analysis also highlights the importance of considering socioeconomic factors like urbanization, diet changes, and healthcare access when developing diabetes prevention and management strategies. The results call for policymakers and healthcare providers to collaborate in addressing the growing public health burden of diabetes in the region.